1992
DOI: 10.3386/w4224
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Earnings Gap: Some International Evidence

Abstract: This paper uses micro-data to analyze international differences in the gender pay gap among a sample of ten industrialized nations. We particularly focus on explaining the surprisingly low ranking of the U.S. in comparison to other industrialized countries. Empirical research on gender pay gaps has traditionally focused on the role of gender-specific factors, particularly gender differences in qualifications and differences in the treatment of otherwise equally qualified male and female workers (i.e., labor ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
298
6
16

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(340 citation statements)
references
References 5 publications
20
298
6
16
Order By: Relevance
“…In analyses not shown, we examined the correlation between the Gini coefficient (measuring the dispersion of household income in society) and the size of the motherhood penalties, and found no relationship between overall income inequality and motherhood earnings penalties. 25 This is notable, given the important impact of income inequality on gender gaps in pay (Blau and Kahn 1992, 1996, 2003Mandel and Semyonov 2005), and suggests that motherhood penalties -earnings gaps between mothers and childless women -cannot be explained or easily attributed to larger economic pressures leading to pay inequalities.…”
Section: Contextual Analysis: Linking Penalties To Policies and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In analyses not shown, we examined the correlation between the Gini coefficient (measuring the dispersion of household income in society) and the size of the motherhood penalties, and found no relationship between overall income inequality and motherhood earnings penalties. 25 This is notable, given the important impact of income inequality on gender gaps in pay (Blau and Kahn 1992, 1996, 2003Mandel and Semyonov 2005), and suggests that motherhood penalties -earnings gaps between mothers and childless women -cannot be explained or easily attributed to larger economic pressures leading to pay inequalities.…”
Section: Contextual Analysis: Linking Penalties To Policies and Culturementioning
confidence: 99%
“…For example, the gender gap in earnings crossnationally is significantly affected by wage distributions (Blau and Kahn 1992, 1996, 2003Mandel and Semyonov 2005). In analyses not shown, we examined the correlation between the Gini coefficient (measuring the dispersion of household income in society) and the size of the motherhood penalties, and found no relationship between overall income inequality and motherhood earnings penalties.…”
Section: Contextual Analysis: Linking Penalties To Policies and Culturementioning
confidence: 99%
“…A series of studies by Blau and Kahn (1992, 1995 have found that to a large extent, the difference in the gender earnings gap across countries can be explained by the difference in the extent of earnings inequality across countries. Blau (1992) illustrates this by first ranking countries by their gender earnings ratios and then ranking countries by their mean female percentile in the male wage distribution.…”
Section: Differences In Wage Structurementioning
confidence: 99%
“…There is a large literature that examines the gender gap in pay within countries and a growing literature that examines the gender gap in pay across countries (see, for instance, Blau and Kahn, 1992, 1995Callan, Adams, Dex, Gustafsson, Schupp, and Smith, 1996). It is taken as given in these literatures that much of the differential between women and men is due to the fact that women bear children and have primary responsibility in most instances for caring or arranging care for them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation